The Influence of Principal Leadership, Organizational Culture, and Academic Supervision on Teacher Performance Through Motivation at State Vocational Schools in Kudus Regency - Pratiwi, Lisa; Wahyudin, Agus; Oktarina, Nina (Educational Management, 2025)
This research aims to examine the influence of principal leadership, organizational culture, and academic supervision on teacher performance, as well as the moderating role of work motivation in these relationships. Teacher performance is reflected in the quality of teaching and learning activities and other institutional duties. Improving teacher performance requires various supports, including effective leadership, a strong organizational culture, adequate academic supervision, and high work motivation. The study employed a quantitative, ex post facto design with a proportional random sampling technique. The sample consisted of 115 teachers from State Vocational Schools in Kudus Regency. Data were collected through questionnaires, and analyzed using path analysis with Moderated Regression Analysis (MRA). The results indicate that principal leadership, organizational culture, and academic supervision each have a positive and significant effect on teacher performance. Furthermore, work motivation was found to strengthen the influence of leadership on performance. However, work motivation did not significantly moderate the influence of organizational culture or academic supervision on teacher performance. These findings suggest that enhancing teacher performance requires not only structural and cultural improvements but also strategies to increase teachers’ work motivation, particularly in supporting effective leadership practices